Navigating the academic borderlands as multiracial and trans* faculty members. Issue 2 (14th March 2020) - Harris, Jessica C.; Nicolazzo, Z
ABSTRACT: Postsecondary institutions remain bastions of oppression, threat and harm for faculty who hold minoritized identities. While some scholars have explored the ways in which monoracial faculty of color and LGBT faculty members navigate an academy that is steeped in racism, genderism, sexism and other systems of oppression, there remains a paucity of scholarship focused on the experiences of multiracial faculty and nonbinary trans* faculty. Given the need to focus on faculty who hold liminal identities in relation to hegemonic identitarian illogic, we used Gloria Anzaldúa's borderlands theory and an auto-ethnographic analysis to explore our academic experiences as faculty members whose identities place us betwixt-and-between socially constructed monolithic identity categories.